Les femmes sans-abri à Montréal - Cabana Renaud, Chrystiane (Université de Montréal, 1983)
Keywords: Femmes; Itinérance

Vers une reconstitution de la vie culturelle des femmes à Montréal dans les années 1940 - Savoie, Chantal (Voix et Images, 2016)
Number: 2
Keywords: Femmes

Femmes, cuisines et consommation de masse au Québec, 1945-1960 - Fradet, Louise (Université Laval, 1989)
Keywords: Alimentation; Femmes

La prostitution de survie chez de jeunes femmes en situation de rue à Montréal - Provencher, Marie-Andrée (Université du Québec à Montréal, 2012)
Keywords: Femmes; Prostitution

Une cité à bâtir: des femmes dans la lutte pour le changement social - Wakeling, Faye (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Femmes; Église Unie

Étude longitudinale sur les modifications du réseau social et des habitudes de vie auprès de femmes socio-économiquement défavorisées - Cotte, Pierre-Marie (Université du Québec à Montréal, 1986)
Keywords: Femmes; Pauvreté

La contribution, le rôle et la place des femmes au Service de préparation au mariage de Montréal, 1944-1972 - Pelletier, Anne (Université de Montréal, 1997)
Keywords: Femmes; Mariage

Les femmes et la ville en temps de guerre et en temps de paix. Montréal dans les années 1940 - Fahrni, Magda (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Guerre

Les conditions de vie des femmes: impact du règlement de location en habitation sociale - Brais, Nicole (Université Laval, 1991)
Keywords: Femmes; Locataires; Logement

La femme mariée en emploi rénuméré: une étude du travail de la femme mariée en emploi rénuméré, au point de vue de ses conséquences sur la femme elle-même, sur le bonheur conjugal ainsi que sur ses enfants d'après les données recueillies dans les enquêtes faites à Montréal en 1956 - Guilbault, Jocelyne; Lafontaine, Andrée; Lacharité, Marie-Thérèse (Université de Montréal, 1956)
Keywords: Famille; Femmes; Mariage; Travail

Les femmes et le rationnement dans La Patrie à l'automne 1942 - Shine, Laura (Les journaux québécois d'une guerre à l'autre. Deux états de la vie culturelle québécoise au XXe siècle, 2018)
Keywords: Alimentation; Femmes; Guerre; Patrie (La)

"Toutes les femmes sont d'abord ménagères" : discours et mobilisations des féministes québécoises autour du travail ménager (1968-1985) - Robert, Camille (Université du Québec à Montréal, 2017)
Keywords: Femmes; Féminisme; Groupes populaires

Toutes les femmes sont d'abord ménagères : histoire d'un combat féministe pour la reconnaissance du travail ménager : Québec 1968-1985 - Robert, Camille (Éditions Somme toute, 2017)
Keywords: Femmes; Féminisme; Groupes populaires

Mères célibataires et infanticides à Montréal 1914-1930 - Lévesque, Andrée (Femmes et justice pénale: XIXe-XXe siècle, 2002)
Keywords: Enfants; Femmes

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre; Joseph; Femmes; Guibord; Joseph; Institut canadien; Mariage; Renaud; Marie-Zoé-Aimée; Trudel; François-Xavier-Anselme; Ultramontains

De cuisinière à gastronome ou comment les représentations du fait alimentaire ont évolué au sein de l'émission Femme d'aujourd'hui de 1965 à 1982 - Demay, Anna (Université du Québec à Montréal, 2018)
Keywords: Alimentation; Radio-Canada; Télévision

Une place à soi? Aspects du célibat féminin laïc à Montréal à la fin du 19e siècle - Renaud, Catherine (Université de Montréal, 1994)
Keywords: Femmes

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Évolution sociodémographique et demande de logements en milieu urbain: le cas de la région métropolitaine de Montréal, 2001-2021 - Codo, Pamphile (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2006)
Keywords: Femmes

Le lesbianisme à Montréal entre 1950 et 1972: une analyse sociologique d'expériences vécues - Chamberland, Line (Université de Montréal, 1994)
Keywords: Femmes

Politique de l’amour dans La Vie en rose (1980-1987): discours et rhétorique de la désobéissance - Bergeron, Marie-Andrée (Recherches sociographiques, 2021)
issued: 2021-05/2021-09
Keywords: Femmes

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

Working for Pay and Managing the Household - Baillargeon, Denyse (Labouring Canada: Class, Race, and Gender in Canadian History, 2008)
Keywords: Femmes; Travail

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Femmes; Mariage

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

Les séparations de corps dans le district judiciaire de Montréal, de 1900 à 1930 - Cliche, Marie-Aimée (Canadian Journal of Law and Society / La Revue Canadienne Droit et Société, 1997)
issued: 1997-21-00
Keywords: Femmes; Mariage

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
issued: 2009-23-00
Keywords: Bourgeoisie; Femmes

Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal - Bradbury, Bettina (University of British Columbia Press, 2011)
Keywords: Femmes; Veuvage

La médicalisation de la maternité au Québec, 1910-1970: autour de la notion de risque - Baillargeon, Denyse (Une démographie au féminin: risques et opportunités dans le parcours de vie / A Female Demography: Risks and Chances in the Life Course, 2009)
Keywords: Femmes; Médecine

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

Entre l'usine et la cuisine (Maison du Fier-Monde, 1984)
Keywords: Femmes; Travail

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Number: 2
Keywords: Famille; Femmes

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Université d'Ottawa, 1991)
Keywords: Femmes; Prostitution

A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920–1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
Number: 2
Keywords: Femmes; Logement

Sur le front intérieur. Les ménagères québécoises de la seconde guerre mondiale: rationnement et récupération - St-Onge, Mélissa (Université de Montréal, 2007)
Keywords: Femmes; Guerre

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Boréal, 1994)
Keywords: Femmes; Prostitution

Solidarity Economy in Montreal: Women's Activism Creating Alternatives Through the Ethics of Care - Germain, L. Marie-France (Université Concordia, 2010)
Keywords: Femmes; Pauvreté

Entre le fantasme et la reconnaissance: étude pastorale de pratiques de prostitution - Nadeau, Jean-Guy (Université de Montréal, 1983)
Keywords: Femmes; Prostitution

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Pigs, Cows, Boarders, and...: Brothels, Taverns, and the Household Economy in Nineteenth-Century Montreal - Poutanen, Mary Anne (Labour / Le travail, 2014)
Keywords: Famille; Femmes

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

Amazons and Victims: Resisting Wife-Abuse in Working-Class Montréal, 1869-1879 - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
Number: 1
Keywords: Femmes; Tempérance

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
issued: 1984-23-00
Keywords: Famille; Femmes

Les recettes de cuisine dans les magazines, des vecteurs de normes? - Laperrière, Jean-Philippe (Gastronomie québécoise et patrimoine, 2013)
Keywords: Alimentation; Femmes

«Toujours je sens mon âme se balancer entre les joies et les peines»: le paysage émotionnel de Marie-Louise Globensky (1849-1919) observé à travers ses écrits personnels - Doucet, Sophie (Université du Québec à Montréal, 2019)
Keywords: Bourgeoisie; Femmes

De vieilles filles à célibataires : une enquête d’histoire orale au Québec, 1940 à 1970 - McNeil, Françoise (Université de Sherbrooke, 2020)
Keywords: Femmes; Mariage

Le discours sur la sexualité, l’alimentation et l’apparence corporelle des adolescentes québécoises durant la décennie 1980 : analyse du magazine Filles d’Aujourd’hui - Dumont-Lévesque, Catherine (Université de Sherbrooke, 2021)
Keywords: Enfants; Femmes

L'Assistance maternelle de Montréal (1912-1961): un exemple de marginalisation des bénévoles dans le domaine des soins aux accouchées - Baillargeon, Denyse (Dynamis, 1999)
Keywords: Assistance maternelle; Femmes

Les politiques familiales au Québec. Une perspective historique - Baillargeon, Denyse (Lien social et Politiques, 1996)
issued: 1996-23-00
Keywords: Enfants; Famille; Femmes

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Contesting Canadian Citizenship. Historical Readings, 2002)
Keywords: Crise; Famille; Femmes

'If You Had no Money, You Had no Trouble, Did You?' Montréal Working-Class Housewives during the Great Depression - Baillargeon, Denyse (Canadian Women. A Reader, 1996)
Keywords: Crise; Famille; Femmes

"Don't I Long for Montreal": l'identité hybride d'une jeune migrante franco-américaine pendant la Première Guerre mondiale - Fahrni, Magda; Frenette, Yves (Histoire sociale / Social History, 2008)
Number: 81
Keywords: Américains; Femmes; Français

Babies for the Nation: the Medicalization of Motherhood in Quebec, 1910-1970 - Baillargeon, Denyse (Wilfrid Laurier University Press, 2010)
Translators: _:n11328
Keywords: Enfants; Femmes; Médecine

If You Had no Money, You Had no Trouble, Did You?': Montreal Working-Class Housewives During the Great Depression - Baillargeon, Denyse (Women's History Review, 1992)
Number: 2
Keywords: Crise; Famille; Femmes

La crise ordinaire: les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Labour / Le travail, 1992)
issued: 1992-23-00
Keywords: Crise; Famille; Femmes

The Historical Record and Adolescent Girls in Montreal’s Red-Light District - Myers, Tamara (Framing Our Past: Constructing Canadian Women’s History in the Twentieth Century, 2001)
Keywords: Enfants; Femmes; Prostitution

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Enfants; Famille; Femmes

Itineraries of Marriage and Widowhood in Nineteenth-Century Montreal - Bradbury, Bettina (Mapping the Margins: The Family and Social Discipline in Canada, 1700-1975, 2004)
Keywords: Femmes; Mariage; Veuvage

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

Travail domestique et crise économique. Les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Université de Montréal, 1990)
Keywords: Crise; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1993)
Keywords: Crise; Famille; Femmes

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 3
Keywords: Famille; Femmes; Veuvage

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Translators: _:n32037
Keywords: Crise; Famille; Femmes

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Rethinking Canada: the Promise of Women's History, 2006)
Keywords: Crise; Famille; Femmes

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Number: 1
Keywords: Avortement; Femmes; Médecine

Conseiller les mères sur l'éducation de leurs enfants pendant l'entre-deux-guerres. Les chroniques d'Odette Oligny - Gratton, Valérie (Université de Montréal, 2015)
Keywords: Enfants; Femmes; Journalistes

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-22-00
Keywords: Enfants; Famille; Femmes

Building the Jewish Community and Claiming “Half the Kingdom”: Women’s Work, Diversity, and Social Justice in Montreal, 1917-2017 - Poutanen, Mary Anne (Juifs d'ici, 2017)
Keywords: Femmes; Juifs; Travail

L’argent ne fait pas le bonheur : les discours sur la société de consommation et les modes de vie à Montréal, 1945-1975 - O'Neill, Stéphanie (Université de Montréal, 2016)
Keywords: Famille; Femmes; Pauvreté

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (University of Manitoba Press, 2010)
Keywords: Famille; Femmes; Italiens

Women in Westmount (The Westmount Historian, 2020)
Number: 2
Keywords: Femmes; Peinture; Élections

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

Counting the Costs of Living: Gender, Citizenship, and a Politic of Price in 1940s Montreal - Fahrni, Magda (Canadian Historical Review, 2002)
Number: 4
Keywords: Alimentation; Femmes; Prix; Épicerie

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

« Empêcher la famille »: Fécondité et contraception au Québec, 1920-60 - Gauvreau, Danielle; Gossage, Peter (Canadian Historical Review, 1997)
Number: 3
Keywords: Contraception; Famille; Femmes; Fécondité

Les Montréalaises à l'école de la nutrition, 1900-1914 - Durand, Caroline (Nourrir la machine humaine. Nutrition et alimentation au Québec, 1860-1945, 2015)
Keywords: Alimentation; Diététique; Famille; Femmes

Rational Meals for the Traditional Family: Nutrition in Quebec School Manuals, 1900-1960 - Durand, Caroline (Edible Histories, Cultural Politics: Towards a Canadian Food History, 2012)
Keywords: Alimentation; Diététique; Famille; Femmes

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

Journaux de "reines du foyer" - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Femmes; Le Normand; Michelle; Mariage

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

Le réseau de régulation sociale montréalais - Fecteau, Jean-Marie; Harvey, Janice (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-39 - Lévesque, Andrée (CHA / SHC, Historical Papers / Communications historiques, 1984)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

L'ajustement social des anciennes de l'Institution des Sourdes-Muettes: une étude du fonctionnement social de 34 sourdes sorties à la fin ou avant la fin de leurs études de cette Institution, entre juin 1951 et juin 1960, habitant la Cité de Montréal - Girard, Jean-Charles (Université de Montréal, 1961)
Keywords: Femmes; Institution des sourdes-muettes; Sourds

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-1939 - Lévesque, Andrée (Delivering Motherhood: Maternal Ideologies and Practices in the 19th and 20th Centuries, 1990)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

Montreal's Network of Social Regulation - Fecteau, Jean-Marie; Harvey, Janice (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
issued: 2021-21-00
Keywords: Bolduc; La; Chanson; Famille; Femmes

"C'est d'abord aux mamans à surveiller les dépenses de la maison": La ligue ouvrière catholique et la consommation quotidienne au Québec, 1939-1954 - Brisebois, Marilyne (Université Laval, 2011)
Keywords: Famille; Femmes; Ligue ouvrière catholique; Prix

''Depuis que l'élément étranger s'est mêlé [...] à la première société française'': dynamiques de genre dans l'espace domestique élitaire canadien au XIXe siècle - Bachand, Marise (Une histoire de la politesse au Québec. Normes et déviances, XVIIe-XXe siècles, 2015)
Keywords: Bourgeoisie; Britanniques; Femmes; Marchand-Dandurand; Joséphine

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Number: 1
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Care of Mothers and Infants in Montreal Between the Wars: the Visiting Nurses of the Metropolitan Life Milk Deposits and Assistance maternelle - Baillargeon, Denyse (Caring and Curing. Historical Perspectives on Women and healing in Canada, 1994)
Keywords: Assistance maternelle; Enfants; Femmes; Goutte de lait; Infirmières

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Des voix étouffées : le travail du sexe à Montréal, d’hier à aujourd’hui - Herland, Karen; Lapointe, Mathieu; Poutanen, Mary Anne (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Criminalité; Femmes; Plante; Pacifique (Plante; Pax); Prostitution; Quartiers

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2. After Confederation, 1986)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (The Social Development of Canada - Readings, 1983)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (CHA / SHC, Historical Papers / Communications historiques, 1979)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Deux rebelles de la fin du siècle: Henriette Dessaulles et Joséphine Marchand - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Dessaulles; Henriette (Fadette); Femmes; Journalistes; Marchand-Dandurand; Joséphine; Mariage

Marriage, Proprety, and the Law in a Square Mile Family: The Case of Annie Stevenson Anderson vs David Morrice, 1884-1885 - Gossage, Peter; Moore, Lisa (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Mariage; Quartiers; Tribunaux

Journaux de jeunes filles: vers un moi autonome - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Mariage; Écrivains

De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime - Smart, Patricia (Les Éditions du Boréal, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Marchand-Dandurand; Joséphine; Mariage; Papineau (famille); Rocbert de La Morandière; Élizabeth (Bégon; Élizabeth)

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-23-00
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde; Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

Le logement communautaire à Montréal: satisfaction résidentielle et insertion socio-spatiale - Morin, Richard; Bouchard, Marie J.; Frohn, Winnie; Bodson, Paul; Chicoine, Nathalie (Canadian Journal of Urban Research / Revue canadienne de recherche urbaine, 2005)
Cet article porte sur l'apport du logement communautaire A la satisfaction residentielle et a l'insertion socio-spatiale des personnes qui y habitent Les auteurs menent d'abord une reflexion generale sur les cooperatives (COOP) et les organismes sans but lucratif (OSBL) d'habitation comme alternative aux logements du marche et aux logements publics. Puis, ils rendent compte des resultats d'une enquete conduite aupres de locataires sans emploi stable, en particulier des jeunes et des femmes a la tete de familles monoparentales, residant dans des logements COOP et OSBL du quartier Hochelaga-Maisonneuve a Montreal. Cette enquete revele des taux eleves de satisfaction residentielle et une insertion sociale, a des degres divers, de ces locataires dans leur voisinage et leur quartier, mais sans etablir une relation directe entre le logement communautaire et le sentiment d'appartenance au quartier.
Number: 2
Keywords: Logement